Management of Tizanidine Withdrawal Syndrome: A Case Report. Issue 11 (13th February 2018) - Suárez-Lledó, A; Padullés, A; Lozano, T; Cobo-Sacristán, S; Colls, M; Jódar, R
Most drugs that act on the central nervous system (CNS) require dose titration to avoid withdrawal syndrome. Tizanidine withdrawal syndrome is caused by adrenergic discharge due to its α2 -agonist mechanism and is characterized by hypertension, reflex tachycardia, hypertonicity, and anxiety. Although tizanidine withdrawal syndrome is mentioned as a potential side effect of cessation, it is not common and there have been few reports. We present the case of a 31-year-old woman with tizanidine withdrawal syndrome after discontinuing medication prescribed for a muscle contracture (tizanidine). She showed high adrenergic activity with nausea, vomiting, generalized tremor, dysthermia, hypertension, and tachycardia. Symptoms were reversed and successful reweaning was achieved by restarting tizanidine followed by slow downward titration. Withdrawal syndrome should be considered when drugs targeting the CNS are suddenly stopped. Weaning regimens should be closely monitored for acute withdrawal reactions.